The structure and chemistry of plastid differentiation during male meiosis in Lilium henryi. - Dickinson, H (1981)
The unusual content of the plastids characteristic of male meiosis and microsporogenesis in Lilium henryi has been investigated using enzymic digestion of material prepared for electron microscopy. Apart from membranous tubules and osmiophilic droplets, commonly regarded as normal constituents of the stroma of undifferentiated plastids, these organelles contained a single conspicuous association between membrane and particulate material and wefts of filaments. Enzymic digestion revealed the membrane-particle association (MPA) to contain RNA and some protein, and the filaments to be entirely proteinaceous. The use of DNase on this material proved both unreliable and, on occasions, unspecific, so no new information has emerged as to the disposition of DNA within these organelles. Many of the plastids divide immediately after meiosis and the MPAs normally divide in step with the organelles. The activities of the MPA and those of the filaments are discussed in terms of changes in the organelle population as a whole, and also in consideration of the fundamental events occurring elsewhere in the cells during the alternation from the diploid sporophyte to the haploid gametophyte.